2021
DOI: 10.1186/s12887-021-02990-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the type of health care sought for symptoms of Acute respiratory infection in children: analysis of Ghana demographic and health surveys

Abstract: Background Globally, acute respiratory infection (ARI) is a leading cause of infant and childhood morbidity and mortality. Currently, it is estimated that 50 million cases of childhood ARI are untreated. In this study, we identified determinants of the type of treatment sought for symptoms of childhood acute respiratory infection (ARI), including non-treatment, amongst a nationally representative sample of children under five years in Ghana. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Consistent with studies reported in Ghana [ 50 ], Bangladesh [ 19 ], and Nepal [ 51 ], maternal education was found significant predictor of health-seeking behavior for symptoms of ARIs among under-five children. This could be due to educated mothers having good access to information on common childhood infections like acute respiratory infections and their symptoms [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with studies reported in Ghana [ 50 ], Bangladesh [ 19 ], and Nepal [ 51 ], maternal education was found significant predictor of health-seeking behavior for symptoms of ARIs among under-five children. This could be due to educated mothers having good access to information on common childhood infections like acute respiratory infections and their symptoms [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 89%
“…Mothers who had big problems with health facilities had a decreased chance of seeking healthcare for symptoms of ARI among children under five compared to mothers where the distance to health facilities was not a big problem. It is in line with previous studies [ 50 , 61 ], this might be because mothers who with a big problem reaching a health facility need to use transportation facilities or travel a long distance to reach the facility, which in turn contributes not to seeking health care for their child [ 62 ]. In addition, mothers who are near the health facility are more likely to visit health care facilities as they are free from transportation costs to reach the health facility [ 13 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 86%
“…The risk of ARI occurrence was statistically higher in mothers with no education or low education than in mothers with higher education. Mothers with higher education are associated with better behavior in seeking treatment when their children are sick [26,27]. Well-educated mother is related to the level of knowledge possessed by mothers, which includes transmission models, symptoms, and danger signs of ARI in the community [28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in terms of the Wealth Index, families with higher wealth status were linked to a greater propensity to seek medical attention from a facility than those with lower wealth status ( 47 , 48 ). This study also revealed one important factor in the decision to seek care in a medical facility was income, and women with money would bring their children to the hospital when they displayed signs of ARI.…”
Section: Discussionmentioning
confidence: 99%